2020
DOI: 10.1016/j.dsx.2020.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Differential white blood cell count in the COVID-19: A cross-sectional study of 148 patients

Abstract: Background SARS-CoV-2 infection alters various blood parameters, which may indicate disease severity and thus help in better clinical management. Aim To study the association between various hematological parameters and disease severity of COVID-19. To analyze the effects of hypertension and diabetes on neutrophil-lymphocyte ratio and neutrophil-monocyte ratio in patients suffering from COVID-19. Materials and methods The study was a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 14 publications
(15 reference statements)
2
42
0
2
Order By: Relevance
“…[20] As for cause-specific survival analysis, we have found even more factors to be associated with the rate of mortality or rate of discharge of a COVID-19 patient. Almost all factors we measured are associated with the rate of event (Table 2, [21][22][23][24][25][26][27][28][29][30][31][32][33][34] The fact that every single one of the factors we found to be significantly associated with rate of mortality/ discharge in Tables 2 and 3 had also been discussed in the literature, not only confirm our findings, but also show an extensive dysregulation in COVID-19 patients. Outpatients, with their zero hospitalization stay time, do not contribute to my analysis concerning stay time.…”
Section: Discussionsupporting
confidence: 85%
“…[20] As for cause-specific survival analysis, we have found even more factors to be associated with the rate of mortality or rate of discharge of a COVID-19 patient. Almost all factors we measured are associated with the rate of event (Table 2, [21][22][23][24][25][26][27][28][29][30][31][32][33][34] The fact that every single one of the factors we found to be significantly associated with rate of mortality/ discharge in Tables 2 and 3 had also been discussed in the literature, not only confirm our findings, but also show an extensive dysregulation in COVID-19 patients. Outpatients, with their zero hospitalization stay time, do not contribute to my analysis concerning stay time.…”
Section: Discussionsupporting
confidence: 85%
“…CRP is made by the liver and elevated level of CRP is a sign of inflammation [ 38 ]. Elevated white blood cell count is indicative of cytokine and immune response, including in COVID-19 infection [ 39 ]. Lymphocyte count is known to be lower in more severe COVID-19 patients and is associated with high mortality rate [ 20 , 24 , 40 42 ] and is associated with hospital-acquired AKI [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on these patients are important. Indeed, many researchers have examined the relationship between severe courses of COVID-19 and white blood cell counts in the body [ 6 , 7 ]. In these studies, it was revealed that some patients with COVID-19 had increased WBC and neutrophil counts with a decrease in lymphocyte count.…”
Section: Introductionmentioning
confidence: 99%
“…The study consisted of data on 148 SARS-CoV-2 infections confirmed by physicians. As a result, they stated that leukocytes, neutrophils, lymphocytes, monocytes and eosinophils, a high neutrophil-monocyte ratio (NMR) and a neutrophil-lymphocyte ratio (NLR), are indicators of disease severity in COVID-19 [ 6 ]. Zhao et al evaluated the clinical findings of COVID-19 patients with increased leukocytes.…”
Section: Introductionmentioning
confidence: 99%